Pictures from the ghetto by Samuel Hirszenberg - Gadowska, Irmina (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
The oeuvre of Lodz-born Samuel Hirszenberg (1865–1908) includes paintings diverse in genre and style: from genre paintings, through portraits, landscapes, to symbolic representations. The article describes selected works with Jewish themes, depicting daily life in the Diaspora, often addressing the ideological crisis experienced by Jewish communities at the turn of the 20th century. The cited excerpts from texts and reviews devoted to the painter, published in the press of the time, provide insight into the reception of the paintings, shedding additional light on how his artistic explorations and achievements were perceived and evaluated.